Assessing ecological integrity: A multi-scale structural and functional approach using Structural Equation Modeling. (December 2016) - Capmourteres, Virginia; Anand, Madhur
Highlights: Structure and function are key to select indicators of integrity. We defined habitat functions and selected potential indicators for it. Using Structural Equation Modeling we tested causal relationships. In a case study we identified five significant structural components for habitat functions. Proposed methodology explores complex interactions and aids ecological monitoring. Abstract: Facing increasing levels of ecosystem degradation, scientists and practitioners aim to preserve ecological integrity — to maintain structures and functions expected of ecosystems in a region. This requires an understanding of the relationship between structural components and functional integrity. In this paper we focused on the study forests of the Credit River Watershed (Southern Ontario, Canada). For this ecosystem we consider one of the major contributors to functional integrity: habitat functions which are defined as the capacity of the ecosystem to provide refuge and reproduction habitat to wild species of plants and animals. We define these 'habitat functions' as a latent variable in Structural Equation Modeling, which allows us to examine its relationship with a number of candidate indicators. We first determined two community-level structural indicators to represent the latent variable: native plant cover and forest bird abundance. We then found underlying causal relationships between multi-scale structural components of the ecosystem and the provision of habitat functions. Three variables at the local scale explain native plant cover — soil nitrogen, soil organic matter, and soil pH. A significant landscape-level variable, patch area, explained native plant cover. Percent natural land cover in a 500 m radius explained forest bird abundance. From a theoretical point of view, this modeling technique allows us to explore complex and simultaneous interactions between structures and functions of ecosystems. As for its practical applications, it can be used to improve ecological integrity monitoring programs by contributing to the selection of meaningful indicators.